2020
DOI: 10.14744/nci.2020.46514
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence (IPV) Types Are Common Among Turkish Women From High Socioeconomic Status and Have Differing Effects on Child Abuse and Contentment With Life

Abstract: OBJECTIVE: Intimate partner violence (IPV) against women is an important public health problem. In this study, we aimed to investigate the exposure of IPV types, child abuse and decrease in life contentment of married women from high socioeconomic status in Turkey. METHODS: Data were collected using an online/written questionnaire and Contentment with Life Scale. The questionnaire included definitions of physical, emotional, economic and sexual IPV and asked how many ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Over half of the studies (n = 18) in this scoping review collected data from samples within the United States [2][3][4][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Three articles came from Turkey [32][33][34], two came from South Africa [35,36] and one article came from Germany [37], Ghana [38], Hong Kong [39], India [40], Malaysia [41], and Palestine [42]. A single article used data collected as part of a multi-country study of China, Cambodia, Papua New Guinea, and Sri Lanka [43].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Over half of the studies (n = 18) in this scoping review collected data from samples within the United States [2][3][4][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Three articles came from Turkey [32][33][34], two came from South Africa [35,36] and one article came from Germany [37], Ghana [38], Hong Kong [39], India [40], Malaysia [41], and Palestine [42]. A single article used data collected as part of a multi-country study of China, Cambodia, Papua New Guinea, and Sri Lanka [43].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…All but two studies [39,41] had entirely female samples. The race/ethnicity of the sample was not documented in 12 studies [30,[32][33][34][36][37][38][39][40][41][42][43]. Six of the studies reported having a sample in which 50% or more identi ed as white [3,4,18,28,29,31].…”
Section: Samplementioning
confidence: 99%
See 3 more Smart Citations